1991
DOI: 10.1080/00071669108417402
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic differences between white leghorns selected for high and low residual food consumption

Abstract: 1. From each of two populations of White Leghorn laying hens, 6 'efficient' and 6 'inefficient' hens were used in energy metabolism studies involving indirect calorimetry with activity measurement. 2. Hens classified as efficient or inefficient with respect to residual food consumption had comparable body weight and production. 3. Efficient and inefficient hens showed similar energy metabolisability, cloacal temperature, shank dimension and egg composition. 4. However, efficient hens produced less heat; activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 6 publications
2
33
0
Order By: Relevance
“…The energy cost related to the standing posture recorded in the present study highlights a major importance of physical activity in the line difference for energy expenditure. This result is consistent with the previously reported lower heat production associated with decreased physical activity in low RFI animals, in laying hens (Luiting et al, 1991), beef cattle (Herd et al, 2004) and pigs (De Haer et al, 1993;Barea et al, 2010;Sadler et al, 2011). Moreover, Lepron et al (2007) reported that the postures and other behaviours partly explained residual ME intake in three pig lines.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The energy cost related to the standing posture recorded in the present study highlights a major importance of physical activity in the line difference for energy expenditure. This result is consistent with the previously reported lower heat production associated with decreased physical activity in low RFI animals, in laying hens (Luiting et al, 1991), beef cattle (Herd et al, 2004) and pigs (De Haer et al, 1993;Barea et al, 2010;Sadler et al, 2011). Moreover, Lepron et al (2007) reported that the postures and other behaviours partly explained residual ME intake in three pig lines.…”
Section: Discussionsupporting
confidence: 92%
“…De Haer et al (1993) reported that the variation in feed intake activity in group-housed growing pigs accounted for 44% of the variation in RFI. Studies in laying hens (Luiting et al, 1991) and beef cattle (Herd et al, 2004) have demonstrated a significant association between general behavioural activity and RFI. However, this has been investigated to a lesser extent in pigs.…”
Section: Introductionmentioning
confidence: 99%
“…As much as 54 % of the difference between efficient and inefficient laying hens in the unaccounted energy expenditure has been attributed to differences in heat production related to physical activity (Luiting et al 1991). Differences in the locomotive activity of young chicks is significantly influenced by genetics and has been shown to be reduced by 6 % in fastgrowing compared to slow-growing broiler breeds (Bizeray et al 2000;Bokkers and Koene 2003).…”
Section: Metabolic Activitymentioning
confidence: 99%
“…It can be postulated that the reduction of this tissue, where cell turnover is high, could lead to a decrease in the energy requirement of the system. Elsewhere, Luiting et al (1991) suggested the difference between efficient and inefficient laying birds in the unaccounted energy expenditure to be in small part attributed to plumage quality; the evidence to suggest that the birds' basal metabolic rate is greatly affected by interactions between feathering and ambient temperature has been presented by Freeman (1971) and later by Carré et al (2008). Observable delays in feathering are displayed in birds selected for high feed intake; Deeb and Cahaner (2001) showed that high heat loss is induced by low feathering in a temperate environment which may lead to low feed efficiency.…”
Section: Metabolic Activitymentioning
confidence: 99%
“…Residual feed consumption, defined as feed consumption adjusted for average size for maintenance and mass of products (e.g., body gain, eggs, and milk) produced, has responded to selection in chickens (Luiting et al, 1991;Bordas et al, 1992;Schulman et al, 1994). Luiting et al (1991) reported that almost 80% of the differences between high and low selection lines were explained by activity-related differences.…”
Section: Response In Litter Size and Its Components Meansmentioning
confidence: 99%